Determination of contract base payments to feeder-pig producers - J L Parcell; Michael R Langemeier (Kansas Agricultural Experiment Station Research Reports, 1996)
Risks associated with independent feeder-pig production have prompted producers to seek alternative production and marketing methods. A means of reducing risk has developed through contract feeder-pig producing. Research results indicate that slightly risk-averse producers required contract base payments ranging from $7.50 to $28.50 per head. Strongly risk-averse producers required contract base payments ranging from $2.50 to $17.75 per head. The lower end of the ranges is for a low-profit producer. The upper end of the ranges is for a high-profit producer.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Risk management; Contract feeder-pig production